KARAKTERISTIK PERKERASAN KAKU DAN PERKERASAN LENTUR DI TINJAU DARI UJI KUAT LENTUR - Iwayan Dermana (Selodang Mayang: Jurnal Ilmiah Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir, 2018)
Road pavement damage within its service period has always been a problem of land transportation. The pavement failure to bear the load is one of the decreasing factors to the pavement durability. It is important to select the appropriate pavement to anticipate such problem. Commonly used pavement types (stiff and flexible pavement) have their strengths and weakness. Therefore, the researcher attempted to study the characteristics of stiff and flexible pavement using the viscocrete-10 additive in mortar and Gilsonite in asphalt reviewed by flexural strength test.